Evaluation of social control in rule-governed behavior or contingency-shaped behavior (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
Research on rule-governed behavior have assessed the effect of social control on the sensitivity of behavior to changes in contingencies after different learning histories (by rules or contingencies). This study systematically replicated Cortez and dos Reis (2008) including monitoring during the task. Eight students undertook a matching-to-sample task. They should respond under control of instructional stimuli (words spoken by the researcher VEK and ZID), which required the choice of comparison similar to the model or different. In Phase 1, four participants underwent contingency learning training (minimum instructions) and four by rules learning (complete instruction). Phase 2 was divided: Blocks 1 and 3, instruction was corresponding; Blocks 2 and 4, differing instruction. Seven of the eight participants reached the criterion in Phase 1 and responded under the control of contingencies in Phase 2. Therefore, the effect of social control on rule following was not observed.
Keywords: rule following; contingency shaped behavior; social control; discrepant rules; contingency sensitivity; matching-to-sample